Optimisation of topical antibacterial preparation from Malaysian kelulut honey by using xanthan gum as polymeric agent - Mohd Amir Shahlan, Mohd Aspar; Raihana Z., Edros; N. A., Hamzah (Malaysian Society of Parasitology and Tropical Medicine, 2021)
The study aims to formulate and optimise topical antibacterial preparation by using Malaysian kelulut honey as the active ingredient and xanthan gum as the polymeric agent. Response surface methodology was used to optimise the preparation. The acidity, honey concentration and xanthan gum concentration were the independent variables. The zone of inhibitions on S. aureus ATCC6538 and E. coli ATCC8739 were the response variables. The optimal preparation was evaluated on its physicochemical properties, viscosity, antibacterial efficacy and stability. The antibacterial efficacy of the optimal preparation was compared to the commercially antibacterial gel (MediHoney™, Comvita). The optimal preparation was formulated at pH of 3.5, honey concentration of 90% (w/v) and xanthan gum concentration of 1.5% (w/v) with the inhibition zones measured on S. aureus ATCC6538 was 16.2 mm and E. coli ATCC8739 was 15.8 mm respectively. The factors of acidity and honey concentration have significantly influenced the inhibition zone on S. aureus ATCC6538 and E. coli ATCC8739. The utilisation of xanthan gum as the polymeric agent was fit for the preparation which showed by adequate physicochemical properties and retained of the antibacterial effects. This was supported by constant viscosity and efficacy of the preparation within the six months of stability study indicating stable and reliable preparation. Xanthan gum is a potential polymeric agent due to its effective use in preparing stable preparation with effective antibacterial properties.